Exploring Careers in Education and Leadership (ExCEL): Outcomes from year one of a high school education camp - Kelly C. Margot; Melissa Pierczynski; Kelly Lormand (Emerald Publishing, 2024)
Purpose - The paper aims to address the increasing issue of teacher shortages and the lack of diversity in America's educators. Highly diverse communities need ways to support community members interested in careers as teachers. This article explores one promising approach to reach and inspire high school students considering the teaching profession. Camp ExCEL (Exploring Careers in Education and Leadership) provided a pathway allowing rising high school seniors an opportunity to explore the teaching profession. This pathway utilized the Grow Your Own framework, recruiting students from a diverse community and providing them resources and information that would further efforts to become an educator within their community. Design/methodology/approach - The current study examined outcomes from an education summer camp, using qualitative thematic analysis to reflexively interpret participants' (n = 29) feelings and beliefs about effective teaching, culturally responsive teaching (CRT), project-based learning (PBL) and their camp experience. Data were collected using Google documents and surveys. The four connected themes that emerged were obstacles and barriers to teaching, qualities of an effective teacher, the impact of culturally responsive teaching and project-based learning on classrooms, and the importance of mentorships within education. Findings - The paper provides insight about how an education camp can support high school students as they explore a career in education. Results suggest that focus on high-quality pedagogy can support student understanding of the career. Students also suggested their perception of effective teaching that includes acknowledging the needs of the whole student, modeling high-quality teaching practices and displaying positive professional dispositions. Research limitations/implications - Because of the chosen research approach, the research results may lack generalizability. Therefore, researchers are encouraged to conduct and examine education camps further. Practical implications - The paper includes implications for the development of other education camps, especially in areas with highly diverse populations. Originality/value - This paper fulfills an identified need to increase the number of persons pursuing a career in education. The focus on a highly diverse community is also an area of need in education. This article details the description of an education camp and the curriculum used, along with findings from data collected during the first year.